A Case Report of Esophageal Bronchogenic Cyst and Review of the Literature With an Emphasis on Endoscopic Ultrasonography Appearance. Issue 11 (March 2016) - Han, Chaoqun; Lin, Rong; Yu, Jun; Zhang, Qin; Zhang, Yang; Liu, Jun; Ding, Zhen; Hou, Xiaohua
Abstract : Abstract: Esophageal bronchogenic cysts are extremely rare. Here we report a more rare type of both presence of intra- and paraesophageal bronchogenic cyst that was safely removed via surgical resection. A 31-year-old male patient with space-occupying lesions in the mediastinum suddenly presented with persistent chest pain for 2 days and then transferred to dysphagia >1 week. Preoperative diagnosis is difficult. Endoscopic ultrasonography (EUS) showed a hypoechoic cystic-solid mass arising from the muscularis propria and local hyperechoic area in the deeper portion of cyst, concomitant with a heterogeneous center and tube-like structure lesion in mediastinum. Turbid coffee color paste contents were aspirated inside the tumor under endoscopic ultrasonography guided-fine needle aspiration (EUS-FNA). A subsequent surgery was performed and histologic finding was diagnostic of esophageal bronchogenic cyst. Immunohistochemical staining confirmed the cyst was positive for carbohydrate antigen 199 (CA199) and carbohydrate antigen 125 (CA125). At a follow-up visit 3 months later, the patient had a regular diet and no complaint. This study is to summarize the clinical manifestations and EUS features of esophageal bronchogenic cyst by retrospectively reviewing the literature and simultaneously to provide guide for the correct examination scheme. The appearance of esophageal bronchogenic cyst can be great variation; EUS seems to be a valuable option for diagnosis and surveillance.